Plataforma WIX como sistema de información de los procesos de la comisión de investigación y desarrollo de la Facultad de Ciencias Jurídicas, Sociales y de la Educación de la Universidad Técnica de Babahoyo - Chamorro Ortiz, Jesus Fabricio (2018)
The Research and Development Commission (CIDE) of the Faculty of Legal, Social and Educational Sciences of the Technical University of Babahoyo; has among its functions with the educational community to keep informed of the work carried out and the programs planned for the execution of the Titling processes, as well as involving other areas: administration, entrepreneurship and research. The Research and Development Commission does not have a mechanism, such as a Web portal, to systematize and organize the information that emanates from the different academic units and dependencies that comprise it; that is why the need arises to develop the Web portal for the Research and Development Commission in order to place at the disposal of the university community and the general public information of interest on the processes of degree and academic activities of the Unit of Titling. The development of the aforementioned portal was estimated as a projective research sustained in a field and documentary design. For its modeling, the proposed methodology for the construction of Web applications using the Wix Platform was used.